The resignification of management processes in care procedures in nursing - Estela Regina Garlet; Letícia de Lima Trindade; Maria Alice Dias da Silva Lima; Ana Lúcia de Lourenzi Bonilha (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This study had as goal to discuss some aspects about the management processes in the care production in nursing. It's made up by a critic reflective analysis, which aims to reflect on the questioning that was brought from the reading of texts used in a doctor and master's course. During the subject's development it was possible to identify, through the analysis of the suggested bibliography, the drifting away visualized by the nurses between the management and the care. However it's possible to conclude that this is due to, in great part to these professionals' graduation, which lead to the distortion on the comprehension of these subjects about the care procedures.